Hymns, prayers and instruction in the Chipewyan language [electronic resource] - Kirkby, W. W. (William West), 1827-1907. (London : Society for Promoting Christian Knowledge, 1881)
Text in Chipewyan. Electronic reproduction. Mode of access: Internet. 44